Zmiany systemu finansowania inwestycji - Ochociński, Stefan (Wydział Prawa i Administracji UAM, 1969)
The proposed changes in the system of financing investments that were resolved at the 2nd Plenum of the Central Committee of the Polish United Workers' Party in 1969, and which are discussed nowadays, schedule a general application of bank credit, a restriction of incidence in auto-financing and a far-reaching desistance from the system of budgetary allowances. The postulated increasing role and significance of bank credit will take place chiefly in the sphere of financing the branch investments, including former central and amalgamation investments and partly the enterprise investments. It is proposed to finance branch investments with economic or technical bank credit. The economic credit, postulated by Z. Fedorowicz, J. Pajestka and M. Kucharski is based on the obligation of refunding the outlays together with interest from the future amortization and profits gained during the exploitation of investment objects. The solutions accepted in the resolution of the 2nd Plenum of the Party and by T. Kierczyński and U. Wojciechowska schedule credit restrictions for the period when the investments are being realized. After they have been finished, a single refund should follow from the investment fund of the amalgamation, formed of profits and amortization of the enterprises, what gives the credit a technical character anticipating means of non-budgetary close-end fund. The resolution of the Party schedules extinguishment of appropriations, and so it does not break with budget altogether. Investments of budgetary units are to be financed with technical credit. This conception does not set distinct limits to auto-financing of investments, but enriches instruments of reacting by the bank in order to shorten the investment cycle and to concentrate investment outlays.
Changes in the System of Financing Investments